Comparison of Experimental and Simulation Studies on Thermal Stratification in a Thermal Energy Storage System - Rao, Gujjar Nagamalleswara; Reddy, K Hemachandra (Journal of Advanced Research in Mechanical Engineering and Technology, 2019)
Renewable energy supplies are steadily gaining increasing importance in all the countries. In particular, solar energy being non-polluting, clean and inexhaustible has received wide attention among scientists and engineers. Though there are many advantages, an important factor is that solar energy is time dependent energy source with an intermittent character. Hence some form of thermal energy storage is necessary for the most effective utilization of this energy source. Most of the thermal energy storage systems in use rely on the specific heat or sensible heat of the storage material, such as water, oil and rock beds and they are known as sensible heat storage systems. Thermal performance of sensible heat storage systems mainly depends on the thermal stratification. Thermal stratification in solar tanks is essential for a better performance of energy systems where these tanks are integrated. The objective of this paper is to study the thermal stratification of energy storage tanks, by means of experiments and computer simulations. The current study is proposed in order to quantify the thermal stratification inside the storage. A special attention is given to the validation of the model considered in this study by using a commercial CFD tool ANSYS WORKBENCH-CFX. Good thermal stratification is vital in order to achieve high thermal performance on solar thermal storages where the tank design is one of the most important elements to accomplish it. As it is known, the best tank design depends on several factors such as the system typology and storage size. In this paper an attempt is made to quantify thermal stratification by considering two such influencing parameters with the help of experiments and computer simulations. With this work, it is possible to conclude what are the important design parameters to build up and best preserve thermal stratification in a solar energy storage tank.